2002
DOI: 10.1182/blood-2002-04-1015
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia proto-oncoprotein MLL is proteolytically processed into 2 fragments with opposite transcriptional properties

Abstract: MLL (mixed lineage leukemia; also ALL-1 or HRX) is a proto-oncogene that is mutated in a variety of acute leukemias. Its product is normally required for the maintenance of Hox gene expression during embryogenesis and hematopoiesis through molecular mechanisms that remain poorly defined. Here we demonstrate that MLL (mixed lineage leukemia) is proteolytically processed into 2 fragments (MLL N and MLL C ) that display opposite transcriptional properties and form an intramolecular MLL complex in vivo. Proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 45 publications
2
129
0
1
Order By: Relevance
“…Recent studies have shown that MLL undergoes proteolytic processing shortly after translation and that this cleavage divides the protein into a larger N-terminal portion (320 kDa) and a smaller C-terminal part (180 kDa) [Yokoyama et al, 2002;Hsieh et al, 2003b]. The enzyme responsible for this processing is Taspase 1, and two cleavage sites are located just upstream of the activation domain [Hsieh et al, 2003a] (Fig.…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…Recent studies have shown that MLL undergoes proteolytic processing shortly after translation and that this cleavage divides the protein into a larger N-terminal portion (320 kDa) and a smaller C-terminal part (180 kDa) [Yokoyama et al, 2002;Hsieh et al, 2003b]. The enzyme responsible for this processing is Taspase 1, and two cleavage sites are located just upstream of the activation domain [Hsieh et al, 2003a] (Fig.…”
Section: Many Pieces Of the Puzzlementioning
confidence: 99%
“…The full-length MLL protein is cleaved by taspase, an aspartic protease, into two fragments MLL-N and MLL-C, which are both core components of MLL complex [13][14][15]. A growing body of evidence has revealed MLL to be a member of a large multi-protein complex that contains proteins involved in chromatin modification/remodeling.…”
Section: Mll and Its Role In Normal Hematopoiesismentioning
confidence: 99%
“…C) heterodimerize through their FYRN and FYRC interaction domains, which have been roughly mapped by two other groups. Yokoyama et al 15 identified two regions within the MLL protein, encompassing the amino acids 1256-2257 (N-terminal domain) and 3610-3745 (C-terminal domain), while Hsieh et al 16 defined regions spanning from amino acids 1978-2161 (N-terminal domain) and 3659-3972 (C-terminal domain). The defined interaction domains included the 40-90-amino-acids-long FYR regions rich in phenylalanine (F) and tyrosine (Y) residues.…”
Section: Introductionmentioning
confidence: 99%
“…13 The AF4-MLL fusion protein is a bona fide substrate for Taspase1, 14 similar to the prototypic MLL protein. 15,16 The resulting protein fragments (AF4-MLL . N and MLL .…”
Section: Introductionmentioning
confidence: 99%